Modeling of outdoor natural ventilation and energy performance for buildings in Woodlands Industrial Park - Liu, Yao (Nanyang Technological University, 2022)
Urban Heat Island (UHI) occurs when temperatures in city areas are much higher than in rural areas. It can be caused by several factors, including reduced natural landscapes, material properties, geometries, and human activities in urban areas. Structures such as buildings and roads retain more heat than rural areas, leading to a significant increase in energy consumption and global warming. Different UHI mitigation techniques have been developed and implemented in the past years. Some examples of such techniques are optimising building design and installing green roofs, cool roofs, and cool pavements. Computational Fluid Dynamics (CFD) is one of the most common numerical simulation methods used to simulate the motion of fluids and UHI effects. In this paper, buildings in the Woodlands Industrial Park of Singapore were studied. Scenarios with different building geometries and arrangements were considered, and CFD simulations were performed to study their effects on UHI. Six case studies were conducted, and the results show that natural outdoor ventilation could be improved by increasing building interval distances and optimising the shape of buildings, leading to lower surface temperatures and enhanced energy performances. • Case Study 1: Building performances are analysed based on the current layout • Case Study 2: Building layouts are rearranged, the interval distance between buildings is increased, and segregated buildings are separated • Case Study 3: Buildings are changed to rectangular shapes with the same length • Case Study 4: Buildings are changed to square shapes • Case Study 5: Buildings are changed to circular shapes • Case Study 6: Heights of buildings are increased